The compatibility of locally available alginate materials with gypsum materials - Taruvingira, A K (My University, 2014)
Purpose: To assess and measure the compatibility of irreversible hydrocolloids (alginates) readily available in South Africa with available gypsum products by testing the quality reproducibility of lines on a standard die. Method: Under controlled laboratory conditions six brands of alginate impression material were tested against six types of gypsum products using the EN 21563:1991 (ISO 1563:1990) recommended protocol. Photomicrographs of the resultant gypsum surfaces were taken and a scoring method similar to that described by Owen (1986b) was used by previously calibrated independent examiners in order to evaluate the acceptable alginate/gypsum combinations. Results: There was an unexpected variability in the rater scores, and considerable variability in the quality of the casts from the various possible alginate/gypsum combinations. Statistical analysis allowed for the use of combination mean scores taking into account all the scores of all the raters, but discrimination was limited to those combinations with the best scores. The best possible score was 3 and the worst 12. In light of the inter-rater variability the combinations with scores of 4 or less were considered to be the recommended combination for clinical application. No alginate proved to be universally compatible with all the gypsum products tested and no gypsum product was universally compatible with all alginates. Conclusion: This study has highlighted the fact that not all alginates are compatible with all gypsum products, and that it is possible to find appropriate combinations for the clinical requirements of a dental cast. However, the fact that there were nine combinations which scored in the very worst category means that manufacturers of alginates should recommend specific gypsum products with which they are compatible and which were used to obtain their ISO rating, and clinicians should be more aware of the need for compatibility.
Keywords: Calcium Sulfate; Alginates; Dental Impression Materials